Obtaining tetraploid plants of ruzigrass (Brachiaria ruziziensis) - Ana Luiza de Oliveira Timbó (Revista Brasileira de Zootecnia, 2014)
The objective of the present work was to induce chromosome doubling in genotypes of Brachiaria ruziziensis with potential for production of good-quality biomass and tolerance/resistance to stress caused by aluminum and spittlebugs. Germinated seeds of B. ruziziensis were immersed in 0.1% colchicine solution for 2 or 3 hours. Ploidy level was determined by flow cytometry and confirmed by chromosome count. Fertility of the tetraploid plants was assessed through evaluation of pollen viability by staining. There was no statistical difference with regard to seedling survival and number of duplicate seedlings between the treatments. Survival rate was 8%, of which 11.45% were tetraploid genotypes. The mean viability of pollen grains from the evaluated tetraploid plants ranged from 51.75 to 55.50%. So, the tetraploids plants obtained from genotypes of a bred population of ruzigrass produce fertile pollen, in percentages that render crosses viable in genetic breeding programs.